2021
DOI: 10.18632/aging.203741
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories and determinants of human fungiform papillae density

Abstract: Tongue fungiform papillae contain taste buds crucial for taste and hormone-producing taste receptor cells; therefore, they may be considered as endocrine organs and have important age-associated physiological implications. We examine the cross-sectional and longitudinal trajectories of fungiform papillae density in 1084 participants from the Baltimore Longitudinal Study of Aging using linear regression models and mixed effects models. At baseline, the mean age was 67.86 ± 14.20 years, with a mean follow-up tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(91 reference statements)
0
3
1
Order By: Relevance
“…Earlier reports on the relationship between sex and the density of FP in adults have shown conflicting findings [29,30]. Karikkineth et al reported that women had a higher fungiform papillae density than men [31]. In our study, we could not confirm a relationship between BMI and the number of FP.…”
Section: Discussioncontrasting
confidence: 92%
“…Earlier reports on the relationship between sex and the density of FP in adults have shown conflicting findings [29,30]. Karikkineth et al reported that women had a higher fungiform papillae density than men [31]. In our study, we could not confirm a relationship between BMI and the number of FP.…”
Section: Discussioncontrasting
confidence: 92%
“…For example, when developing sugar-free foods with bitter notes, they could target male consumers in advertisements, as female consumers are more likely to be supertasters. While some studies reported females to have more fungiform papillae and taste buds [38,39], others found that females perceived PROP intensity higher than males [40,41]. Furthermore, it was found that females perceived the bitter intensity significantly higher than males, therefore females were observed to be the majority of super-tasters [42].…”
Section: Demographic Characteristicsmentioning
confidence: 97%
“…We also examined the cross-sectional and longitudinal trajectories of FP density in 1,084 participants from the Baltimore Longitudinal Study of Aging using linear regression and mixed effects models ( 414 ). At baseline, the mean age was 68 years, with a mean follow-up time among those with repeat visits of 4 years.…”
Section: Research In Progressmentioning
confidence: 99%